Applying related arts as an important part of training conductors at universities - Фурдак, Тетяна (Pedagogy of Higher and Secondary Education, 2014)
Furdak T. D. Applying related arts as an important part of training conductors at universities. The article highlights issues as for using related arts in teaching future music teachers, in particular at classes in conducting art. The author proves the role of synthesis of choreographic and dramatic art in this process. The author also states that aesthetic community of these arts has significant similarities.